Teacher Efforts and The Characteristics Of Islamic Religious Education Teacher In Improving Students' Reading Ability - Rani Darmasari; Wahab (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
The background of this research is the teacher's efforts related to how a teacher is able to understand and determine the boundaries that must be carried out by a teacher in organizing material, interacting, and carrying out learning processes for students of SDN 09 Nanga Sayan. This is good, marked by enthusiastic participation direct learning, asking questions and answering teacher questions, and paying attention to the teacher during learning. This is what makes researchers interested in conducting more in-depth research. This research is focused on (1) How are the Efforts of Islamic Religious Education Teachers and Characteristics in Students of SDN 09 Nanga Sayan for the 2022/2023 Academic Year? (2) How is the Ability to Read the Qur'an in Students of SDN 09 Nanga Sayan for the 2022/2023 Academic Year? (3) What are the Efforts of Islamic Religious Education and Character Education Teachers in Improving the Ability to Read the Qur'an in Students of SDN 09 Nanga Sayan for the 2022/2023 Academic Year?This research is a type of descriptive research with a qualitative approach. Data collection procedures carried out are using observation techniques, interviews, and documentation. Researcher interviews were conducted with ethics subject teachers.Based on the results of the study, it can be concluded as follows: (1) The efforts of Islamic Religious Education and Characteristics Teachers to instill a sense of enthusiasm and also provide motivation in various ways, moreover teaching children who are just learning to read the Qur'an is something that is certain. not easy. (2) Students' Ability to Read the Qur'an in SDN 09 Nanga Sayan found that there are some children who can read the Qur'an and some who cannot read the Qur'an. (3) Efforts of Islamic Religious Education and Moral Education Teachers in Improving Al-Qur'an Reading Ability at SDN 09 Nanga Sayan by repeating hijaiyah letters such as the letter ba, what it looks like in front, what it looks like in the middle and what it looks like at the end